PENAMBAHAN LARUTAN DAUN BINAHONG DALAM AIR MINUM TERHADAP KUALITAS FISIK DAGING AYAM BROILER FASE FINISHER (Addition of binahong leaf solution in drinking water on physical quality of finisher phase of broiler chicken) - Anthonius A. Abraham; Herowati T. Pangestuti; Markus Sinlae (Universitas Nusa Cendana, 2021)
This study aims to examine the effect of giving a solution of binahong leaves (Anredera cordifolia) in drinking water on the physical quality of broiler chicken meat finisher phase. A total of 72 broiler chickens strain CP 707 produced by PT Charoen Phokphan Indonesia. This study used a completely randomized design (CRD) with 4 treatments and 6 replications. The treatments consisted of R0: drinking water without binahong leaf solution, R1: drinking water + 20 ml of binahong leaf solution/liter of water, R2: drinking water + 30 ml of binahong leaf solution/liter of water, R3: drinking water + 40 ml of binahong leaf solution / liter of water. The results of analysis of variance and Kruskal wallis showed that the treatment had no significant effect (P>0.05) on meat pH, water holding capacity, tenderness, and cooking loss of broiler chicken. Based on the results of this study, it can be concluded that the addition of binahong leaf solution with a level of 20 mL/liter of water, 30 ml/liter of water, 40 ml/liter of water has not had and effect on the physical quality of the finisher phase broiler chicken meat.